Impact dynamics of composite beams - Yigit, A.S.; Christoforou, A.P. (Composite structures, 1995)
The dynamics of a composite beam subject to transverse impact is investigated. A linearized contact law based on an elastic-plastic contact is shown to yield excellent results for the impact response. A dynamic ratio which is defined as the ratio of the maximum impact force obtained from the dynamic simulation to the one obtained from a half-space analysis (i.e., local contact) is used to characterize the type of impact response i.e., whether it is locally dominated, quasi-static or dynamic. It is found that this ratio depends on a single nondimensional parameter called ‘dynamic impact number’, which also governs the initial impact response until the waves are reflected back from the boundaries.